PENGARUH METODE DISKUSI DALAM MENGEMBANGKAN MULTIPLE INTELLIGENCE SISWA KELAS VIII MTS PAB 1 HELVETIA - Siti Khodijah (Taushiah: Jurnal Hukum, Pendidikan dan Kemasyarakatan, 2021)
Intelligence is something that is considered for students, this involves verbal-linguistic intelligence, interpersonal intelligence, being able to use words orally and in writing well, being able to work together and understand other people. The method is the way taken to achieve certain goals, and discussion is the negotiation or exchange of ideas to gain an understanding of the causes of a problem and the solutions to it. Multiple intelligences are multiple intelligences as this theory explains that human cognitive competition is better explained in terms of a set of abilities, talents, or mental skills called intelligence. According to Gardner, this view is more human and accurate in reflecting data on human intelligent behavior. The use of the discussion method is quite helpful in developing multiple intelligence for class VIII students of Mts PAB 1 Helvetia.